Experimental study on cyclic settlement of piles in silt soil and its application in high-speed railway design. (March 2021) - Chen, Yunmin; Ma, Shengnan; Ren, Yu; Chen, Renpeng; Bian, Xuecheng
Highlights: Large-scale model testing of piles in silt under static and cyclic loading are conducted. A chart approach is proposed to judge the development trend of pile's cyclic settlement. Unitization of the proposed approach is demonstrated by a case study of pile-supported high-speed railway embankment. Abstract: Pile-supported embankment is popularly used for constructing high-speed railways on soft soils. With train running at high speed, the dynamic load on the pile top generated by the train passages increases noticeably. To keep the long-term settlement of the railway track within a reasonable range, it is necessary to investigate the settlement of piles in soils simultaneously subject to the monotonic load caused by the weight of the track structure and embankment as well as the cyclic load caused by the train passages. In this paper, model tests on piles in silt soil under combined monotonic and cyclic loading were conducted. The behavior of a pile in saturated silt was investigated by measuring pile settlement, soil pressure on the pile surface, and pore water pressure in the soil adjacent to the pile. Based on the model testing results, the ratio of the mean value of cyclic load to the ultimate bearing capacity of the pile ( P m / P u ) and the ratio of the half amplitude of the cyclic load to the ultimate bearing capacity of the pile ( P cyc / P u ) were identified as the main factors dominating the development of pile settlement. A higher P cyc / P u leads to faster accumulation in the pile settlement, and a higher P m / P u facilitates this process. A chart with three zones determined by the combination of P cyc / P u and P m / P u has been proposed to distinguish the settlement trends of the piles: stable zone, metastable zone and unstable zone. The combination of P cyc / P u and P m / P u located in the stable zone generates very small settlement. Moreover, for the loading combination in the metastable zone, an analytical model was proposed to predict the cyclic pile settlement subject to cyclic load with large cycles. The advantage of the model is that the coefficient of friction at the pile surface and the cyclic strain degradation parameter are incorporated. Finally, a case study is presented to demonstrate the application of the proposed chart and the prediction method on cyclic pile settlement in the design of piled embankment of high-speed railways.